Ehlers–Danlos Syndrome : an underdiagnosed condition - Cumarasamy, Rubini; Mohd Hanafi, Mohd Sharil Iman; Che' Man, Mohamad (2019)
• Failure to thrive is a common clinical presentation that is usually discovered during routine child visit at primary care clinic. • The pitfall arises when there are overlapping causes in which nutritional and psychosocial issues mask the suspicion of medical cause. • A well-looking child with failure to thrive is considered as normal variants of growth or having nutritional deficiency without proper assessment. • Ehlers-Danlos Syndrome (EDS) is a clinically and genetically heterogeneous group of hereditary connective tissue disorders (HCTD) that involves a genetic defect in collagen and connective tissue synthesis and structure5. It is generally characterised by joint hypermobility, skin hyperextensibility and tissue fragility. • Despite being a genetic disorder either by autosomal dominant or recessive, the established diagnosis is usually delayed during adolescent or adulthood. • The International EDS Consortium 2017 proposed a revised EDS classification which recognized 13 subtypes with distinct set of clinical criteria.